Unsupervised Feature Extraction for Time Series Clustering Using Orthogonal Wavelet Transform - Zhang, H.; Ho, T.B.; Zhang, Y.; Lin, M.-S. (Informatica)
Unsupervised Feature Extraction for Time Series Clustering Using Orthogonal Wavelet Transform